2019
DOI: 10.1590/1984-0462/;2019;37;3;00017
|View full text |Cite
|
Sign up to set email alerts
|

Inactive Behavior in Adolescent Students of the Brazilian Western Amazon

Abstract: Objective: To identify the prevalence of physical inactivity in adolescent students in the city of Porto Velho, RO, Northern Brazil, and its associated factors.Methods: School-based study, conducted with 2,694 adolescents. The self-reported variable for outcome was physical inactivity. Factors associated with inactive behavior were verified by multiple logistic regression. The independent variables were inserted into the model in hierarchical blocks.Results: The overall prevalence of inactive behavior was 39.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…According to Ferreira et al 13 , the highest percentage of active transportation use was found in the northern region of Brazil, followed by the southern region. In contrast, among the studies selected for this review, the study that presented the lowest use of active transportation was precisely in a city located in the northern region of Brazil, Porto Velho-RO 20 . Despite the controversial results between the studies, both the study by Ferreira et al 13 and that by Farias et al 20 used data from youth in the network public and private education, however Ferreira et al 13 considered data from all capitals in the northern region, while Farias et al 20 only from the Porto Velho-RO region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ferreira et al 13 , the highest percentage of active transportation use was found in the northern region of Brazil, followed by the southern region. In contrast, among the studies selected for this review, the study that presented the lowest use of active transportation was precisely in a city located in the northern region of Brazil, Porto Velho-RO 20 . Despite the controversial results between the studies, both the study by Ferreira et al 13 and that by Farias et al 20 used data from youth in the network public and private education, however Ferreira et al 13 considered data from all capitals in the northern region, while Farias et al 20 only from the Porto Velho-RO region.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, among the studies selected for this review, the study that presented the lowest use of active transportation was precisely in a city located in the northern region of Brazil, Porto Velho-RO 20 . Despite the controversial results between the studies, both the study by Ferreira et al 13 and that by Farias et al 20 used data from youth in the network public and private education, however Ferreira et al 13 considered data from all capitals in the northern region, while Farias et al 20 only from the Porto Velho-RO region. Therefore, it is possible that youth in Porto Velho present a different reality from youth in other capitals in the northern region.…”
Section: Discussionmentioning
confidence: 99%